2014
DOI: 10.1080/10255842.2014.936856
|View full text |Cite
|
Sign up to set email alerts
|

Contact of dual mobility implants: effects of cup wear and inclination

Abstract: Cup wear and inclination on the pelvic bone are significant factors, which change the contact of the articulating surfaces, thus, impacting the long-term performance of hip implants. This paper presents a finite element (FE) analysis of the contact of the dual mobility implants under the influence of cup wear and inclination. A 3D FE model of the implant was developed with the application of equivalent physiological loading and boundary conditions. Effects of cup inclination angle ranging from 45° to 60° and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…This may be due to the general biomechanical concept of dual mobility liners. The current literature suggests that the primary articulation is involved in most everyday movements, whereas the secondary articulation only moves during endrange of motion and experiences lower contact stresses [11,12,15]. This suggests that slight differences in clearance might clinically be less important.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This may be due to the general biomechanical concept of dual mobility liners. The current literature suggests that the primary articulation is involved in most everyday movements, whereas the secondary articulation only moves during endrange of motion and experiences lower contact stresses [11,12,15]. This suggests that slight differences in clearance might clinically be less important.…”
Section: Discussionmentioning
confidence: 94%
“…88.9 % of clearances are above the clearance used in a recent 3D FE analysis [13] Arch Orthop Trauma Surg (2015) 135:1177-1181 1179 primary articulation. Uddin et al [12] used a 3D FE to analyze a clearance of 0.200 mm for the secondary articulation. Contact pressure on the secondary articulation was also found to be much lower than on the primary articulation.…”
Section: Discussionmentioning
confidence: 99%
“…The outer surface of the cup is fixed, ie, no displacement in x, y, and z directions is allowed. It is reported that, for a hard‐on‐hard bearing couple, the inclusion of the metallic shell and the pelvic bone models embedded onto the outer surface of the cup has a negligible influence on the contact pressure and stress in the cup . Hence, only the cup and head models are considered for simplicity and computational efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that, for a hard-on-hard bearing couple, the inclusion of the metallic shell and the pelvic bone models embedded onto the outer surface of the cup has a negligible influence on the contact pressure and stress in the cup. 21,22 Hence, only the cup and head models are considered for simplicity and computational efficiency. A frictional contact between the head and the cup with a coefficient of friction, μ, of 0.09 is employed.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent improvements in design, manufacturing and surgical technique led to a resurgence in use, until it declined once again when some metal‐on‐metal (MoM) hip articulations were found to cause clinical problems related to design flaws. Trunnionosis at the modular head‐neck taper was also recognized as a problem with conventional MoM bearing hip arthroplasty, and has been abandoned as a current surgical option . Hip resurfacing with MoM bearings however continues to this day (trunnionosis is not an issue), although its usage has declined.…”
Section: Introductionmentioning
confidence: 99%